Digital Fable Containing Asking and Giving Opinion to Stimulate Critical Thinking in EFL learners’ Speaking - Salma Nuraulia; Dedeh Rohayati; Luthfiyatun Thoyyibah (Universitas Galuh, 2026)
This study aims to measure the effectiveness of digital fables and analyze EFL students’ perceptions of digital fables containing asking and giving opinions to stimulate critical thinking in EFL learners' speaking. The population and sample consisted of eighth-grade students at a junior high school in Tasikmalaya. The method used was a mixed method with an explanatory model. Quantitative data were collected using a quasi-experimental design and data collection through pre-tests and post-tests on the control group and experimental group. Qualitative data used a case study design, with data collection through EFL learners' perceptions from interviews. The results of the hypothesis testing showed that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected, with a p-value of 0.011 < 0.05, indicating that the results were effective. To measure the level of effectiveness, the N-Gain result was used, yielding a value of 51%, indicating that the results fall into the “less effective” category. Although the quantitative results indicate less effectiveness, the qualitative data show positive student responses, as they improved self-confidence, motivation, and enjoyment in learning. Therefore, the researcher suggests using digital fables in other subjects to enhance student enthusiasm.